STUDENTS’ READINESS OF THE IMPLEMENTATION OF FACE-TO-FACE LEARNING AT ENGLISH CLASS IN THE ACADEMIC YEAR 2021/2022 - Tira Nur Fitria (Universitas Islam Negeri Alauddin Makassar, 2022)
This research aims to know the students’ readiness for limited face-to-face learning in English class in ITB AAS Indonesia in the academic year 2021/2022. This research is descriptive qualitative. The result shows that : (1) approval of the implementation of limited face-to-face learning shows that 65 % of students agree about the implementation of limited face-to-face learning in the academic year 2021/2022. 2) Students’ readiness for the implementation of limited face-to-face learning shows that 1) 75 % of students strongly agree to participate in vaccination activities before joining/participating in limited face-to-face learning activities. 2) 60 % of students strongly agree to take part in limited face-to-face learning to a maximum of 50% of students in one classroom. 3) 70 % of students strongly agree to keep the distance between the seats in English class. 4) 70 % of students strongly agree to avoid crowds both before and after English class. 5) 85 % of students strongly agree to use 3 (three) layers of cloth or disposable masks/surgical masks that cover the nose and mouth when in the campus area and English class. 6) 90 % of students strongly agree to maintain hygiene and health protocols by measuring body temperature, washing hands with soap, and using hand sanitizer when entering campus or English class. 3) Students’ expectation to learn English in the odd semester in the academic year 2021/2022. It shows that 85 % of students agree to learn English in both face-to-face learning and online learning (Blended Learning)”. Related to the students’ choice of online media in face-to-face learning, 65 % of students choose Zoom Meeting besides face-to-face learning. Even though the implementation of learning, the institution still must continue to prioritize the health and safety of campus residents (students, lecturers, education staff) and the surrounding community. In lectures, practicum, studio, field practice, or other forms of learning, the university must meet several conditions.